Effect of azolla supplementation in feed on semen freezability in bucks - GANGWAR, CHETNA; KUMAR, RAVINDRA; KHARCHE, S D; JINDAL, S K; CHAUDHARY, U B; MISHRA, A K (The Indian Journal of Animal Sciences, 2019)
The present study was conducted to evaluate the effect of azolla supplementation on semen freezability in Barbari bucks. Ten adult Barbari bucks (2–4 years old) were selected, and divided into control and treatment group (5 bucks in each group) as per completely randomized design. Bucks of control group were fed with 400 g concentrate pellet/day along with 6–7 h grazing while bucks of treatment group were supplemented with 100 g fresh azolla along with 400 g concentrate pellet and 6–7 h grazing. Semen ejaculates (8) were collected from each buck of control and treatment groups after 60 days of azolla supplementation. Immediately after collection, semen samples were evaluated for colour, volume, density, mass motility, progressive motility, live sperm count, acrosomal integrity and hypo-osmotic swelling positive spermatozoa. Then semen samples were diluted with tris–citric acid fructose diluents having 6% (v/v) glycerol as cryoprotective agent and 10% (v/v) egg yolk. After equilibration, semen samples were filled in straws and vapour frozen for 10 min 4 cm above the liquid nitrogen and finally stored into liquid nitrogen container. Post thaw motility, live sperm count, abnormalities, acrosomal integrity and hypo-osmotic swelling test were conducted to check the effect of azolla feeding on the freezability. Post thaw motility, live sperm count, acrosomal integrity and hypo-osmotic swelling positive spermatozoa were significantly higher in treatment group. It could be concluded that dietary azolla supplementation to breeding bucks improved the quality and freezability of semen favouring the use in artificial insemination program.